Q: X3 - 5x2 - 13x - 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5x^2 - 13x = x(5x - 13)

5x2-8x-4

To factorise x3 + 5x2 - 16x - 80 I note that -80 = 5 x -16 and 5 & -16 are the coefficients of x2 and x. Thus I have: x3 + 5x2 - 16x - 80 = (x + 5)(x2 - 16) and the second term is a difference of 2 squares, meaning I have: x3 + 5x2 - 16x - 80 = (x + 5)(x + 4)(x - 4)

x(x - 13)(x - 1)

x3 + 13x2 + 42x = x(x2 + 13x + 42) = x(x2 + 6x + 7x + 42) = x[x(x + 6) + 7(x + 6)] = x(x + 7)(x + 6)

Related questions

2x3 - 7 + 5x - x3 + 3x - x3 = 8x - 7

5x^2 - 13x = x(5x - 13)

x2 • (5x2 + x + 8)

5x2-8x-4

To factorise x3 + 5x2 - 16x - 80 I note that -80 = 5 x -16 and 5 & -16 are the coefficients of x2 and x. Thus I have: x3 + 5x2 - 16x - 80 = (x + 5)(x2 - 16) and the second term is a difference of 2 squares, meaning I have: x3 + 5x2 - 16x - 80 = (x + 5)(x + 4)(x - 4)

x3 + 5x2 - x - 5 = (x2 - 1)(x + 5) = (x + 1)(x - 1)(x + 5)

x(x - 13)(x - 1)

x(x - 1)(x - 13)

x(x - 13)(x - 1)

x3 + 13x2 + 42x = x(x2 + 13x + 42) = x(x2 + 6x + 7x + 42) = x[x(x + 6) + 7(x + 6)] = x(x + 7)(x + 6)

2x2 - 13x - 7 = (2x + 1)(x - 7)

5x2 + 3x + 8x2 = 13x2 + 3x = x(13x + 3)